Gold nanoparticles functionalized with PEGylate uncharged porphyrins. (June 2017) - Mineo, P.; Abbadessa, A.; Mazzaglia, A.; Gulino, A.; Villari, V.; Micali, N.; Millesi, S.; Satriano, C.; Scamporrino, E.
Abstract: Porphyrin functionalized Au nanoparticles show many interesting applications and many efforts have been devoted to the assembly of charged porphyrin structures in order to improve their water solubility. In this work, we report on the functionalization of gold nanoparticles with porphyrin modified in meso-positions with uncharged polyethylene glycol chains in order to obtain nanosystems soluble both in water, and in some non-aqueous media. The functionalization steps were monitored by some spectroscopic techniques such as UV–Vis, steady-state and time resolved fluorescence and dynamic light scattering. The final functionalized Au nanoparticles were characterized by scanning transmission electron microscopy and X-ray photoelectron spectroscopy. These modified gold nanoparticles showed the porphyrin characteristic emission properties and were effective for 1 O2 generation. Finally, the laser scanning confocal microscopy results demonstrated a sub-cellular localization of the porphyrin-functionalized gold nanoparticles, with the maintenance of the porphyrin-characteristic emission properties. Graphical abstract: Highlights: The AuNPs functionalized with PEGylate porphyrins were obtained by a bottom-up approach. Functionalized nanoparticles showed the porphyrin characteristic emission properties. Nanoparticles were effective for 1 O2 generation. The laser scanning confocal microscopy demonstrated a sub-cellular localization.